Tenosynovial Giant-Cell Tumors of the Foot and Ankle: A Critical Analysis Review. Issue 1 (17th January 2017) - Fraser, Ethan J.; Sullivan, Martin; Maclean, Fiona; Nesbitt, Alexander
Abstract : Tenosynovial giant-cell tumor (TGCT) is the common term used to describe a group of soft-tissue tumors that share a common etiological link. Historically, the multiplicity of terms used to describe these tumors, in addition to contention regarding etiology, has led to confusion regarding their diagnosis and treatment. An overexpression of colony-stimulating factor-1 (CSF-1) caused by a specific chromosomal translocation t(1;2) has been identified in both localized and diffuse tumors and has led to an interest in pharmacological therapies targeting the CSF-1/CSF-1R (CSF-1 receptor) axis. Operative treatment remains the mainstay of treatment for TGCT of the foot and ankle; however, given the rarity of these tumors, treatment recommendations have not been verified on the basis of large cohort studies or high-level evidence. A multidisciplinary approach is important in TGCT treatment. Open surgical excision or synovectomy is considered to be the first-line treatment. While the roles of arthroscopic excision, radiation therapy, and targeted pharmacological therapies have not been validated, these therapies may be of use for selected patients, particularly those with recurrent or unresectable lesions. A clear definition of tumor recurrence based on radiographic evidence of progression and/or return of symptoms is required to quantify the outcomes of treatment, to reduce heterogeneity between studies, and to avoid morbidity associated with repeated surgical excisions.